TI_GERICHTE 12.2004.79 vom 6. April 2005 , locazione - valore litigioso - disdetta per mora - inizio del termine di diffida - onere della prova - TI Tribunale d'appello (2005)
locazione - valore litigioso - disdetta per mora - inizio del termine di diffida - onere della prova